Family business succession planning in South Africa: a daughter’s perspective - Nonkwelo, Palesa Ruth (My University, 2019)
Family businesses make significant contributions to various economies across the globe. This study highlights the importance of succession planning in small, medium sized and large family businesses. As such, they face a challenge on succession when the owner needs to pass over the managerial powers to another family member. The phenomenon has the potential to bring down the business if proper measures are not instituted throughout the process. The situation is complicated when the successors are women who are traditionally viewed as incapable of handling senior positions in the family business. To enable the success of a woman successor, there must be a cordial relationship between the owner, the successor, and the other family members. Given the crucial role that family businesses play in the South African economy, it is necessary that the succession issues are researched and measures developed to avert disputes. This study researches the various factors that affect succession in family businesses. The findings help in widening the understanding of the dynamics involved when determining the possible successor of the business. They will successfully influence policy-making processes, add to the existing business knowledge, educate people on the business succession matters and make practical recommendations for actions that families can take to improve their chances of a successful succession and thereby ensure the sustainability of the family business for future generations. The quantitative study used a cross-sectional research design to collect primary data using online questionnaires. The sample was identified using convenience total sampling and snowball technique. The data was then analysed using IBM SPSS Statistics 95, t-Test, and Regression Analysis. The results confirmed a relationship between a cordial parent-daughter relationship and a smooth transition. This implies that it is necessary for a parent to cultivate a cordial relationship between family members to prevent the collapse of the family business. The study also revealed that there is no relationship between daughter gender factors in succession planning as the literature review had suggested.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation, 2019
Keywords: Family-owned business enterprises; Fathers and daughters--South Africa